ENRICHING VOCABULARY THROUGH SOCIAL INTERACTION MODEL - Siti Maryam Hamid (Universitas Muhammadiyah Makassar, 2015)
The objective of this research was to find out the significance of the students’ achievement before and after learning vocabulary through Social Interaction Method at the eight class of SMP Guppi Samata Gowa. This research employed pre-experimental method with one group pretest and posttest design. There were two variables, namely dependent variable was the students’ vocabulary achievement and the independent variable was the application of Social Interaction Model in teaching vocabulary. The population was the students in the eighth grade of SMP Guppi Samata Gowa. The sample of the research consisted of 50 students which were taken by using cluster total sampling, 25 students were taken as an experimental class and 25 students were taken as a controlled class. The instrument was vocabulary test in the multiple-choice test. The multiple choice test consists of 10 items that consist of five choices. The findings of the research were students vocabulary used pre-test and post-test. The result of the data indicated that there was a significant difference between students’ post-test in experimental class and controlled class. The mean score of posttest (61.6) in experimental class was greater than the mean score of posttest (56) in controlled class and the standard deviation of posttest (8.94) in experimental class was greater than the standard deviation of posttest in controlled class (6.29). From t-test, the researcher found that the value of t-test (2.553) was greater than t-table (2.021) at the level of significance 0.05 with the degree of freedom (df) = 48.